2004
DOI: 10.1177/0363546503261699
|View full text |Cite
|
Sign up to set email alerts
|

Does Immobilization after Radiofrequency-Induced Shrinkage Influence the Biomechanical Properties of Collagenous Tissue?

Abstract: Careful rehabilitation is imperative after radiofrequency-induced shrinkage. This animal model supports an immobilization period of at least 6 weeks after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This is supported by the findings of Potzl, 41 who reported that the therapy with electromagnetic fields is a complex method which can improve metabolism of bone tissues and its structures through slowing or preventing loss of bone because of the re-creation of the piezoelectric effect and building of bone substance due to the activation of calcium metabolism and stimulation of calcium deposits in the bone, indirect effects of PEMF due to regulation of the hormone system, which plays a crucial role in regulating the metabolism of minerals, and improvement of overall well-being and increased activity will have a positive impact on symptoms of osteoporosis.…”
Section: Discussionsupporting
confidence: 77%
“…This is supported by the findings of Potzl, 41 who reported that the therapy with electromagnetic fields is a complex method which can improve metabolism of bone tissues and its structures through slowing or preventing loss of bone because of the re-creation of the piezoelectric effect and building of bone substance due to the activation of calcium metabolism and stimulation of calcium deposits in the bone, indirect effects of PEMF due to regulation of the hormone system, which plays a crucial role in regulating the metabolism of minerals, and improvement of overall well-being and increased activity will have a positive impact on symptoms of osteoporosis.…”
Section: Discussionsupporting
confidence: 77%
“…Joint capsular tissue with decreased stiffness is more easily deformable, indicating that an early loss of joint stability may occur if the joint is subjected to a constant strain. This study and others 34,35 have suggested that the RF-altered tissue and joint should be protected from excessive motion for at least 6 weeks after surgery.…”
mentioning
confidence: 53%
“…This stiffness reduction after RF use was also reported by other authors in animal experiments and in other biological structures. (19)(20)(21) Stiffness loss is noticeable by a major increase of maximum deformity of the structure as shown by the assay. The PCL presented a mean increase of 4.6±0.6 mm, while the PL showed 6.30±0.6mm increase, both with p<0.001.…”
Section: Discussionmentioning
confidence: 81%